THE COMPARISON BEST CORRECTION VISUAL ACQUITY (BCVA) BETWEEN SPECTACLES AND SPHERICAL RIGID GAS PERMEABLE (RGP) IN HIGH ASTIGMATISM PATIENTS: Poster Presentation - Observational Study - Resident - Rino Agustian Praja; Rinda Wati (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objective : Rigid Gas Permeable (RGP) toric contact lenses are generally considered in patients with high astigmatism, while spherical RGP contact lenses are present as an alternative option that can be used and still provide optimal results in patients with high astigmatism. Methods : A cross-sectional study was conducted at DR M Djamil Hospital Padang in January 2021 to December 2022 period. Inclusion criteria were patients who went to the eye clinic at DR M. Djamil Hospital in January 2021 to December 2022 period, patients with high astigmatism ? -2.00 D underwent correction vision with spectacles and RGP spherical contact lenses. Results best correction visual acquity (BCVA) compared between spectacles and spherical RGP contact lenses. Samples must meet the inclusion and exclusion criteria. Data is collected and analyzed using statistical applications. Results : 49 patients with high astigmatism corrected with spectacles and contact lenses showed data distribution was 15 men (30.6%) and 34 women (69.4%). Most age in the age group 20-29 years 24 people (49%). BCVA with spectacles obtained a median of 0.18 and an RGP of 0.00 based on LogMar. Mann whitney test showed significant difference between BCVA wearing glasses and RGP spherical contact lenses with a value of p = 0.006 right eye p = 0.009 left eye (p <0.005) Conclusion : Spherical RGP contact lenses can still be used in patients with high astigmatism if we don’t have toric RGP trial. Spherical RGP contact lenses show better BCVA results than spectacles in high astigmatism patients.